Rheological Properties of Blood and Physical and Chemical Indicators of Erythrocytes in Healthy Individuals of Different Age Groups (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In practically healthy people of mature age of the first and second periods - from 18 to 59 years, the rheological properties of blood and indicators of the physical and chemical properties of erythrocytes are stable. In elderly people, 60 years and older, blood viscosity increases, red blood cell aggregation increases, their deformation decreases, density and dry matter content increase, the amount of water in red blood cells decreases, and the permeability of red blood cell membranes decreases.